ANALISIS STRUKTUR SEKTOR INDUSTRI PROVINSI NUSA TENGGARA BARAT MENGGUNAKAN ANALISA INPUT-OUTPUT (I-O ANALYSIS) - Muhammad Nurjihadi; Abdul Hadi Ilman; Zulkieflimansyah Zulkieflimansyah (JURNAL CAFETARIA, 2023)
This article aims to provide a structural analyses to determine which manufacturing subsectors are considered to be leading subsectors in the manufacturing industries of West Nusa Tenggara Province (NTB). Identifying leading manufacturing subsectors is important to develop strategies in improving the performance of manufacturing industries in NTB Province. Type of data used in this research was secondary data that was obtained from several relevant sources such as the bureau of statistics (BPS), the office of industry in NTB Province, and others. Result of the research revealed that foods and beverages industry was confirmed to be the leading industrial subsector in West Nusa Tenggara Province. Others industries that are potential to be leading subsectors in NTB manufacturing sector are basic metal industry, wood industry, and non-metal mineral industry.